Some modifications of Sarrus’s rule method via permutation for finding determinant of 4 by 4 square matrix - Karim, Sharmila; Ibrahim, Haslinda; Omar, Zurni (IP Publishing LLC, 2016)
Sarrus rule is well known method for finding determinant of square matrix.This method is also known as a cross multiplication method.However this method is not applicable for n > 3.With this motivation, we attempt to extend this method by employing some modifications using permutation for the case of 4 by 4 square matrix